2017
DOI: 10.3389/fphar.2017.00765
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Use Correlates with Reduced Risk of Gallstones in Diabetic Patients: A 12-Year Follow-up Study

Abstract: Objective: Few studies are available on the association between gallstones and metformin use. The objective of the study was to determine whether metformin use is associated with gallstones.Methods: A population-based retrospective cohort study was conducted using the database of the Taiwan National Health Insurance Program. Subjects of newly diagnosed diabetes mellitus were included from 2002 to 2013. The metformin-exposure group was defined as ≥29 cumulative defined daily dose (DDD) of metformin use. The un-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…A retrospective cohort study showed a significant reduction in the incidence of gallstones in diabetic patients on long-term metformin. 39 Our study similarly found that diabetics had a 27% increased risk of gallstones compared to non-diabetics (in Model 4). However, the precise mechanism by which AIP enhances the susceptibility to gallstones, as well as the significance of diabetes about this correlation, remains uncertain.…”
Section: Discussionsupporting
confidence: 71%
“…A retrospective cohort study showed a significant reduction in the incidence of gallstones in diabetic patients on long-term metformin. 39 Our study similarly found that diabetics had a 27% increased risk of gallstones compared to non-diabetics (in Model 4). However, the precise mechanism by which AIP enhances the susceptibility to gallstones, as well as the significance of diabetes about this correlation, remains uncertain.…”
Section: Discussionsupporting
confidence: 71%
“…In a population-based study involving 36 patients with polycystic ovary syndrome and 20 healthy controls, metformin treatment was associated with an improved metabolic and hormonal imbalance associated with polycystic ovary syndrome and increased gallbladder motility ( Isik et al, 2012 ) that is associated with a lower risk of cholesterol gallstones ( Pauletzki et al, 1996 ). A cohort study in diabetes also observed a reduced risk of gallstones in individuals with >180 cumulative defined daily dose of metformin compared to those with <29 cumulative defined daily dose of metformin ( Liao et al, 2017 ). Even though these findings nominally are conflicting with our findings, several issues in previous studies deserve consideration, including lack of direct GDF-15 measurement, unadjusted important confounders (e.g., smoking status), no examination of the nonlinearity of the association, and certain special features of the diabetic population and patients with polycystic ovary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by the fact that diabetes control can affect the incidence of cholelithiasis. A retrospective cohort study demonstrated a significant reduction in gallstone formation among diabetic patients with long-term use of metformin [ 32 ]. In addition, Liu et al .…”
Section: Discussionmentioning
confidence: 99%